Exploring Ageism: The Lived Experiences of Older Adults in Community Settings, Bengkulu City, Indonesia - Nova Yustisia; Titin Aprilatutini; Encik Putri Ema Komala; Bardah Wasalamah; Desi Dwi Siwi Atika Dewi; Mahmasoni Masdar (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Ageism poses a serious threat to healthy aging and remains under-researched in low- and middle-income countries. In Indonesia cultural traditions emphasize deference to elders through rituals and honorific language. At the same time, older adults often find themselves sidelined when real decisions are made in families and community groups. This stark contrast between symbolic respect and practical exclusion necessitates a more in-depth examination of the mechanisms of ageism in daily life and the responses of elderly individuals to it. This study examined the ways in which ageism affects elders in Bengkulu City, Indonesia, and how they actively resist its impact. Methods: This study is a qualitative phenomenological design using in-depth semi-structured interviews that are analyzed using Colaizzi’s seven-step method. Interview transcripts were analyzed using Colaizzi's seven-step method. Purposive sampling was used to determine the participants. The total number of participants involved was 20 people aged 61-75 years (mean = 67.75, SD = 3.78), with the majority of respondents being female in Bengkulu City, Indonesia (June–September 2024). Trustworthiness increased by credibility, dependability, transferability, and confirmability. Results: This study produced four primary themes and sixteen sub-themes. Elders are venerated symbolically yet marginalized in home and community decision-making processes. Secondly, numerous individuals embrace silence and emotional suppression as a reaction to internalized ageist beliefs. Third, ageism connects with gender and socioeconomic disadvantage, exacerbating marginalization, especially for older women who serve as caretakers. Their aspirations for dignified aging highlight the necessity for dependable income, accessible healthcare, and legal protections against ageism. Conclusion: Addressing ageism in this context requires action at multiple levels. Practitioners and policymakers should empower older adults in decision-making, promote intergenerational dialogue, design gender-sensitive social protections, integrate spiritual support into elder services, and introduce robust anti-ageism legislation. By moving beyond ceremonial respect to genuine inclusion, societies can honor older adult’s contributions and ensure their dignity.